2008
DOI: 10.1111/j.1365-2648.2007.04509.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students’ perceptions of the importance of caring behaviors

Abstract: Further research is needed, using longitudinal designs, to explore nursing students' perceptions of caring behaviours in different cultures, as well as evaluation studies of innovations in curriculum and teaching methods to improve learning in relation to cultural competence and caring concepts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
5
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 31 publications
(56 reference statements)
4
63
5
3
Order By: Relevance
“…The findings were also consistent with the study of Khademian and Vizeshfar (2008). The monitoring subscale (M= 4.33, SD ±0.60), a type of instrumental skill, was rated by students as the most important which is equivalent to domain one (1) in this study.…”
Section: Resultssupporting
confidence: 91%
“…The findings were also consistent with the study of Khademian and Vizeshfar (2008). The monitoring subscale (M= 4.33, SD ±0.60), a type of instrumental skill, was rated by students as the most important which is equivalent to domain one (1) in this study.…”
Section: Resultssupporting
confidence: 91%
“…Spiritual needs of patients and families are sometimes not discussed within the multidisciplinary team (Saliba and Baldacchino 2010;Khademian and Vizeshfar 2007). This is resultant from various factors including confusion between religion and spirituality and lack of role clarity.…”
Section: Recommendationsmentioning
confidence: 99%
“…According to some authors, this is because for years nursing theory has claimed care as the central axis of nursing practice (Sargent 2012). Nonetheless, its definition remains complex and ambiguous (Khademian & Vizeshfar 2008, Sargent 2012. Alberdi (1992) has shown that in spite of the focus on care in definitions of nursing, providing care continues to be difficult in practice because of an overload of tasks related to procedures, diagnosis or equipment (Lleixá et al 2009).…”
Section: Care and Its Implementationmentioning
confidence: 99%
“…According to the International Council of Nurses (2002), "Nursing encompasses autonomous and collaborative care of individuals of all ages, families, groups and communities, sick or well and in all settings". That is, there is a consensus on a theoretical level that establishes care as the essence and main function of nursing (Morse et al 1990, Alberdi 1992, Khademian & Vizeshfar 2008, Begum & Slavin 2012, Sargent 2012, Labrague et al 2015.…”
Section: Introductionmentioning
confidence: 99%